Development of Learning Videos with Kinemaster-Based Stop Motion Animations on Thematic Learning in Elementary Schools - Sa'diah, Halimatus; Zulhendri, Zulhendri; Fadriati, Fadriati (Universitas Islam negeri Mahmud Yunus Batusangkar, 2022)
This study aims to produce learning videos with stop motion animation based on kinemaster for thematic learning in elementary schools that are valid and practical. This type of research is development research with a 4-D development model (define, design, develop and disseminate). The research instruments used were learning video validation sheets and practicality sheets (teacher and student response questionnaires). The data analysis technique used is descriptive analysis. Based on the experts' assessment, the results of learning videos with stop motion animation based on kinemaster were in a very valid category and student response questionnaires were in a very practical category. Thus learning videos with stop motion animation based on kinemaster in thematic learning can be used in the learning process in elementary schools.